Ten Principles for Interpreting Neuroscientific Pronouncements Regarding Human Nature - Weissenbacher, A. C. (2015)
As the field of brain research continues to advance, much is being discovered about the various aspects of the brain that are associated with certain feelings, thoughts, and behaviors. However, certain studies, or popularized accounts thereof, overreach in their pronouncements, drawing unwarranted conclusions regarding human nature. There are ten principles that will assist the non-specialist in critically assessing both now and future discoveries reported from the neurosciences, with a focus on helping theologians using neuroscientific data in multidisciplinary work regarding human nature.
Keywords: brain scan limitations; critique of neuroscience; fMRI; Free Will; Neurotheology